11β-Hydroxysteroid dehydrogenase 2: A key mediator of high susceptibility to osteoporosis in offspring after prenatal dexamethasone exposure. (January 2022) - Wu, Zhixin; Wen, Yinxian; Xiao, Hao; Zhu, Jiayong; Li, Bin; Shangguan, Yangfan; He, Hangyuan; Wang, Hui; Chen, Liaobin
Abstract: Epidemiological investigations have shown that individuals treated with dexamethasone during pregnancy have an increased risk of osteoporosis after birth. Our studies reported that peak bone mass was decreased in the prenatal dexamethasone exposure (PDE) offspring before chronic stress, while further decrease was observed after chronic stress. Simultaneously, increase of bone local active corticosterone was observed in the PDE offspring, while further increase was also observed after chronic stress. Moreover, the histone H3 lysine 9 acetylation (H3K9ac) level of 11-beta hydroxysteroid dehydrogenase 2 (11β-HSD2) and its expression in bone tissue of PDE offspring rats remained lower than the control before and after birth. Injection of 11β-HSD2 overexpression lentivirus into the bone marrow cavity could partially alleviate the accumulation of bone local active corticosterone and bone loss induced by PDE. In vitro, dexamethasone inhibited the expression of 11β-HSD2 and aggravated the inhibitory effect of corticosterone on the osteogenic differentiation of bone marrow-derived mesenchymal stem cells (BMSCs). Overexpression of 11β-HSD2 partially alleviated the inhibitory effect of corticosterone. Moreover, dexamethasone promoted the nuclear translocation of glucocorticoid receptor (GR), which resulted in the stimulation of 11β-HSD2 expression due to the binding of GR to the 11β-HSD2 promoter region directly, as well as increasing H3K9ac level in the 11β-HSD2 promoter region by recruiting histone deacetylase 11 (HDAC11). Our results indicated that low expression of 11β-HSD2 in bone tissue is an important mediator for the high susceptibility to osteoporosis in PDE adult offspring. Graphical Abstract: ga1 Highlights: PDE causes high susceptibility to osteoporosis in adult offspring. Low-expressional 11β-HSD2 mediates the high susceptibility to osteoporosis in PDE adult offspring. GR/HDAC11 signal participated in the inhibitory effect of dexamethasone on 11β-HSD2 expression.